Presence of the peroxisomal 22-kDa integral membrane protein in the liver of a person lacking recognizable peroxisomes (Zellweger syndrome). - Lazarow, P B (1986)
Peroxisomes have not been detected in liver and kidney of patients with Zellweger syndrome. Some peroxisome proteins are missing; others are present in normal amounts but are located in the cytosol. We have prepared an antiserum against the 22-kDa integral membrane protein characteristic of rat liver peroxisomes. The antiserum crossreacts with the human liver counterpart, which likewise has a mass of 22 kDa. By immunoblot analysis, we demonstrate that the 22-kDa protein is present in normal amount in Zellweger liver and is integral to a membrane. The result suggests that peroxisome membranes are assembled in Zellweger syndrome but may be defective for the import of matrix proteins. As a result, newly synthesized proteins are left in the cytosol, where some persist and others are degraded. Lacking their usual content, such aberrant peroxisomal membranes would be unrecognizable morphologically. Immunoblot analyses also showed that the peroxisomal hydratase-dehydrogenase is deficient in Zellweger kidney as well as liver, but catalase is present in both organs.